Transmitting scalable video coding using VLC with color and dimming control to assure QoS. (March 2015) - Han, Doohee; Lee, Kyesan; Lee, Kyujin
Abstract: Recently, light emitting diode (LED) technology has been the focus of the information technology and green technology industries. The visible light communication (VLC) system uses LED technology for simultaneous illumination and data transmission. Therefore, the VLC system provides illumination to the user, which can provide both high quality multimedia services and various application services. The main concerns of VLC systems are illumination and bit error rate (BER) performance. Consequently, it is necessary to analyze the illumination control and method of transmitting multimedia data in the VLC system. In this paper, we propose a method to effectively transmit and Red, Green, Blue (RGB) three-color LED to video signal while providing dimming and color control from the VLC system. In the VLC system, LEDs can generate various colors of light by controlling the mixing ratio of each individual RGB color element. Thus, each RGB channel will have a different signal power, and each channel will have different performance. Therefore, we present a novel resource allocation using the RGB channel state information to allocate the multi-layers of video in the VLC system. The conventional system allocates the fixed channel to a scalable video coding (SVC) signal. However, the proposed system allocates a high priority to the SVC signal channel. As a result of computer simulation tests, the proposed system can improve the BER performance compared to the conventional system.